Особливості поширення та щільність населення перлівницевих (Mollusca, Bivalvia, Unionidae) водних об’єктів української частини басейну Прип’яті - Васільєва, Людмила; Vasilieva, Liudmyla (Східноєвропейський національний університет імені Лесі Українки, 2014)
Фауна перлівницевих української частини басейну Прип’яті представлена шістьма видами. Для досліджу¬ваних гідроценозів властиві поселення, утворені 3−4 видами Unionidae. Найвищу зустрічальність має U. pictorum, найнижчу – A. cygnea і P. complanata. Щільність населення перлівницевих коливається у межах 1−11 екз./м2. The Unionidae Rafinesque, 1820 fauna in the Prypiat basin in Ukraine is represented with six species: Unio pictorum Linnaeus, 1758, U. tumidus Philіpsson, 1788, U. crassus Philіpsson, 1788, Anodonta anatina Linnaeus, 1758, A. cygnea Linnaeus, 1758 и Pseudanodonta complanata Rossmässler, 1835. In the researched hydrocoenosis simplified populations out of 3−4 Unionidae species prevail. The highest occurrence is in U. pictorum mollusks, the lowest – in A. cygnea and P.complanata. The Unionidae population density is within 1−11 sp./m2. The decrease of population density, the low occurrence of some species, the prevailence of simplified Unionidae family populations in water objects of the researched basin are the result of general hydrocoenosis degradation in Ukraine. The preservation of Unionidae diversity and quantity is impo¬ssible without the protection of their habitats and water resources restoration. In present-day situation of historically compiled Unionidae biot demage and complete absence of protection programmes for Unionidae, which are powerful biofilters, the declaration at some Prypiat basin territories nature reserve fund of Ukraine is necessary.
The Distribution and Density Peculiarities in Unionidae (Mollusca, Bivalvia, Unionidae) Populations in Water Objects of the River Prypiat Basin in Ukraine
Keywords: перлівницеві (Unionidae); поширення; зустрічальність; щільність населення; природно-заповідний фонд; Unionidae; distribution; population density; occurrence; nature reserve fund